The Leadership, Trust, and Openness to Experience as Antecedents of Performance of Sports Manufacturing Firms of Thailand, Exploring the Mediating Role of Team Cohesion - Mochammad Fahlevi; Kittisak Jermsittiparsert; Navaporn Wongsuwan; Mohammed Aljuaid; Thitinan Chankoson; Phutthiwat Waiyawuththanapoom, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The performance of the organizations needs to be measured. This study aimed to determine the relationship between openness, trust, leadership, team cohesion, and organizational performance. This study was cross-sectional, and survey questionnaires were used to collect data from participants. The questionnaire was distributed to employees of Thai organizations that manufacture sports goods. For this purpose, convenience sampling was used, and 75.78 percent of the responses were usable. For data analysis, PLS 3.3.2 was utilized. According to the study's findings, trust does not affect team cohesion. Additionally, team cohesion does not mediate between confidence and performance. However, the remaining relationships were deemed significant. The study's findings are beneficial for policymakers and academics.